HALAIK THE RELIGION OF TAU TAA VANA - Muhammad Hisyam (LIPI Press, 2015)
Tau Taa Vana is a minority ethnic group living in Dataran Tinggi Bulang, Central Sulawesi. There are around 1500 inhabitants. They believe in Pue, their only God, and practice Halaik, a local customary religion. According to them, custom (adat) is the same as religion. Halaik, literally means belief. For the people of Tau Taa Vana, custom, tradition, and traditional medication are united as a religion system. Kapongo is the main ritual that provides offerings (sesaji) consisting of betel, areca nut, and lime to the super natural essence or Pue. These offerings are delivered in every special occasion, such as hunting, planting, harvesting, medicating, building house, and ceremonial feast. However, they have no church, no temple, and no regular worship. They can pray anytime and anywhere in various ways. Halaik is a genuine belief that has been practiced by Tau Taa Vana since a long time ago. In the past five decades, however, some of them have converted to be Muslims as well as Christians. Nevertheless, to the present days they still faithfully practice Halaik, their old religion. Keywords: Halaik, Kapongo, Pue, Dataran Tinggi Bulang